2004
DOI: 10.1016/j.soilbio.2004.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activities in forest soils exposed to chronic depositions from a lignite power plant

Abstract: Atmospheric emissions of fly ash and SO 2 from lignite-fired power plants strongly affect large forest areas in Germany. The impact of different deposition loads on the microbial biomass and enzyme activities was studied at three forest sites (Picea abies (L.) Karst.)along an emission gradient of 3, 6, and 15 km downwind of a coal-fired power plant (sites Ia, II, and III, respectively), representing high, moderate, and low emission rates. by the content of organic C and cation exchange capacity, while those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…This parameter shows the highest values on the site which is localized at the centre of peatbog, where carbon mineralization is very fast and decreases with increasing depth. These results agree to those of other authors (Maková et al 2011;Klose et al 2004), and from various types of ecosystems.…”
Section: Resultssupporting
confidence: 94%
“…This parameter shows the highest values on the site which is localized at the centre of peatbog, where carbon mineralization is very fast and decreases with increasing depth. These results agree to those of other authors (Maková et al 2011;Klose et al 2004), and from various types of ecosystems.…”
Section: Resultssupporting
confidence: 94%
“…Besides the possibility of direct destruction of the microbial biomass and changes in organic matter quality, pH related changes in community structure, especially changes in fungi to bacteria ratios have to be taken into account (Ba˚a˚th and Anderson 2003). Klose et al (2004) suggested a relationship between fungi to bacteria ratio and microbial biomass C to soil organic C ratio. However, Bauhus and Khanna (1999) suggested that microbial biomass C to soil organic C ratios below 5 (g C mic kg À1 C org ), as found here, could be caused by acidity more than by consumable parts of soil organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…As abovementioned, we found some positive correlations between soil pH and enzyme activities. Previous reports have also described positive correlations between soil pH and urease (Ekenler and Tabatabai, 2004), acid phosphatase (Klose et al, 2004), arylsulphatase (Wang et al, 2006), dehydrogenase (Rodríguez-Loinaz et al, 2008) and b-glucosidase (Acosta-Martínez and Tabatabai, 2000;Wang et al, 2006). In contrast, many authors (Acosta-Martínez and Tabatabai, 2000;Dick et al, 2000;Wang et al, 2006;Rodríguez-Loinaz et al, 2008) have reported a negative correlation between soil pH and acid phosphatase.…”
Section: Soil Enzyme Activitiesmentioning
confidence: 96%